Costs of moderate to severe chronic pain in primary care patients – a study of the ACCORD Program - Lalonde, Lyne (Dove Medical Press, 2014)
BACKGROUND: The economic burden of chronic noncancer pain (CNCP) remains insufficiently documented in primary care. PURPOSE: To evaluate the annual direct health care costs and productivity costs associated with moderate to severe CNCP in primary care patients taking into account their pain disability. MATERIALS AND METHODS: Patients reporting noncancer pain for at least 6 months, at a pain intensity of 4 or more on a 0 (no pain) to 10 (worst possible pain) intensity scale, and at a frequency of at least 2 days a week, were recruited from community pharmacies. Patients’ characteristics, health care utilization, and productivity losses (absenteeism and presenteeism) were documented using administrative databases, pharmacies’ renewal charts, telephone, and self-administered questionnaires. Patients were stratified by tertile of pain disability measured by the Brief Pain Inventory questionnaire. RESULTS: Patients (number =483) were, on average, 59 years old, mainly women (67.5%), and suffered from CNCP for a mean of 12 years at an average pain intensity of 6.5±1.9. The annual direct health care costs and productivity costs averaged CAD $9,565 (±$13,993) and CAD $7,072 (±$11,716), respectively. The use of complementary health care services accounted for almost 50% of the direct health care costs. The mean adjusted total direct health care costs (considering pain-related hospitalizations only) and productivity costs increased with more pain disability: low disability, CAD $12,118; moderate, CAD $18,278; and severe, CAD $19,216; P=0.001. CONCLUSION: The economic burden of CNCP is substantial and increases with the level of pain disability, which suggests the need for and potential benefits of improving CNCP management through specific and adapted treatment plans targeting the impact of pain on daily functioning.